STUDI KINERJA STRUKTUR BETON BERTULANG SISTEM GANDA DENGAN PEREDAM YIELDING METALLIC DAMPER TERHADAP BEBAN GEMPA KUAT - Setiawan, Andri
Earthquake has become one of the main considerations in the planning of infrastructure in many countries in recent years. Infrastructure which is not well planned will be damaged, causing severe casualties. Conventional methods are generally performed on earthquake resistant building by designing building to be more rigid by adding components such as shear walls or through capacity design which is often referred as the "strong column weak beam" method. This conventional methods dissipate seismic energy through the process of damage or commonly known as the plastification mechanism of the structural elements which are planned to be damaged. This method is considered less effective and efficient because the main structural elements of the building will be still suffered with permanent damage which is difficult to repair after the earthquake. This is the main reason for continuing studies to find new methods to improve the performance of the structure more effectively and efficiently against strong earthquakes. One of the results of research that went into effect on earthquake resistant buildings is hysteretic damper (yielding metallic dampers). Hysteretic damper was first introduced by R. Skinner, J. M. Kelly, and A. J. Heine in 1973 in Physics and Engineering Laboratory New Zealand's Department of Scientific and Industrial Research. This damper utilizing hysteretic nature of the metal on the condition of post-elastic deformation to dissipate energy. Under moderate earthquakes (small deformations), a hysteretic damper acts as a stiff member that helps to resist structural deformations, whereas under severe earthquakes (large deformations) it acts as an energy absorber. Hysteretic damper are capable of improving the earthquake performance of a structure by increasing its stiffness, its strength, and its ability to dissipate energy. Performance of the structure which is being simulated in this study is consist of roof displacement, total story drift, inter-story drift, base shear, the proportion of energy, and plastic joint damage that occurs in the main structure. Performance checking method which is used in this study is nonlinear time history analysis using time history earthquake data from El-Centro NS component (1940) scaled to the Bandung area with medium soil based on SNI 1726-2012. El-Centro earthquake NS component (1940) which is used in this study is only the first 10 seconds alone because the intensity of the earthquake occurred in this range is maximum. Model of the structure which is reviewed in this study consists of two main models. The first model is the dual system structure while the second model is the dual system structure which is equipped with hysteretic dampers. Hysteretic damper is applied to the structure with chevron brace combined with inverted-v configuration. The main variables of interest in this study is the property of hysteretic dampers consisting of yield strength, elastic stiffness, and post-elastic stiffness. In this present study will be used seven models which is equipped with different hysteretic dampers property. Results of the analysis showed that the application of hysteretic dampers on the structure will tend to reduce the value of roof displacement, total story drift, and inter-story drift. While the base shear forces on the structure are likely to increase but the increase was compensated by energy dissipation through hysteretic dampers. In addition, the application of hysteretic dampers will also change the proportion of energy in the structure. Energy dissipation of hysteretic dampers able to absorb most of the seismic energy input so the potential energy which is representing major structural damage can be minimized. This fact is further strengthened by the results of the analysis which is proven that the amount of plastic hinge which suffered damage on the main structure also decreased significantly. Effectiveness of this hysteretic damper increases with increasing damping properties are used. Results of analysis stating that the performance of the structure will continue to increase along with the increase in the value of yield strength and stiffness of the dampers. This is also seen in the seventh models which is equipped with hysteretic dampers which have the largest value of yield strength and stiffness properties will have the smallest deformation and less structural damage. In this study, obtained the results of the analysis showed that there will be a saturation point when the addition of hysteretic dampers is no longer causing significant impact to the structure’s performance, even the main structure will still be damaged which can not be eliminated. In this study conducted an alternative solution to treat the condition by doing retro-fitting process on major structures. This process could be done by increasing the amount of reinforcement on the elements which were damaged. Analysis results prove that the solution can eliminate damage to the main structure which is considered more effective and efficient when compared to the addition of the dampers.